Mobile augmented reality for computer-assisted percutaneous nephrolithotomy - Müller, Michael; Rassweiler-Seyfried, Marie-Claire; Klein, Jan; Seitel, Alexander; Gondan, Matthias; Baumhauer, Matthias; Teber, Dogu; Rassweiler, Jens; Meinzer, Hans-Peter; Maier-Hein, Lena (International journal of computer assisted radiology and surgery, 2013)
Percutaneous nephrolithotomy (PCNL) plays an integral role in treatment of renal stones. Creating percutaneous renal access is the most important and challenging step in the procedure. To facilitate this step, we evaluated our novel mobile augmented reality (AR) system for its feasibility of use for PCNL.
Gesehen am 22.06.2021